Regulatory Uncertainty, Corporate Structure, and Strategic Agendas: Evidence from the U.S. Renewable Electricity Industry - Dutt, Nilanjana; Joseph, John (Academy of Management Journal, 2019)
Prior research has demonstrated that although organizations generally avoid uncertainties, this behavior is not universally true. To better understand the contingencies around organizations’ responses to regulatory uncertainty, we consider the influence of corporate structure on attentional processing. Our theory and findings suggest that because corporate structure differentiates their problem-solving and learning activities, headquarters and subsidiaries differ in attention allocation on their strategic agendas. Our results show that headquarters display lower levels of uncertainty aversion than do subsidiaries, but all organizations generally make greater shifts in attention toward alternative courses of action if they possess complementary experience and access shared experience. We test these ideas using a sample of U.S. electric utility companies attending to renewable technologies from 2000 to 2010—a market greatly affected by regulatory uncertainty. By linking models of decision making under uncertainty and learning with the attention-based view, we develop a more comprehensive understanding of the ways uncertainty influences organizational attention.